Post-Delivery Recovery Until All Women's Reproductive Organs Recover After Delivery (Postpartum Period 6 - 8 Weeks) Regarding Knowledge Of Umbilical Cord Care In Postpartum Mothers - Ernawati, Ernawati; Ula, Zumrotul; Muthoharoh, Binti Lulu; Rahmat, Rezqiqah Aulia; Saad, Rahmiyani; Devin, Devin; Wati, Isra (International Journal of Health Sciences, 2025)
The postpartum period or puerperium or postpartum period is the period or time that begins after baby born until 6 Sunday. Mother postpartum experience adaptation Which divided in the talking in phase is when the mother is in a period of dependency, focused on herself, and the mother is uncomfortable with physical changes. Talking hold phase, in this phase the mother feels worried about not being able to care for her baby. The goal of umbilical cord care is to identify early and prevent bleeding. This study is a descriptive study with the main objective to describe the knowledge of postpartum mothers about umbilical cord care. The data in this study are primary data and secondary data. Based on the results of the study of postpartum mothers' knowledge about "understanding umbilical cord care" in the Health Center Area in Palopo, most respondents answered correctly. This data collection was obtained from the results of the study, namely Subjective data and Objective data. Subjective data or symptoms are phenomena experienced by the client and may be the beginning of the client's normal sensation habits. Objective Data, based on phenomena that can be seen factually. Objective data can be observed and measured. This data will provide evidence of the patient's clinical symptoms and facts related to the diagnosis. The knowledge of postpartum mothers about umbilical cord care in the Health Center Area in Palopo is mostly included in the good category, but this good knowledge is not in line with good behavior in umbilical cord care. Therefore, suggestions for health workers in providing information on umbilical cord care are accompanied by correct umbilical cord care practices.